An Epidemiological and Biochemical Perspective on Motorcycle Road Traffic Accidents - Hanniya Naveed, Naila Jabeen Iqbal, Bisma Qadeer, Fatima Tahir, Tariq Hussain, Sonia Nisar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Motorcyclists are prone to injuries due to road traffic accidents causing a high burden on health department. Objectives: To access the burden and pattern of injuries associated with motorcycle related road traffic accidents in the Emergency department of Sheikh Zayed Hospital Rahim Yar Khan. Methodology: A Total of 372 patients of road traffic accident were included in this cross sectional study from 1st March 2023 to 31st August 2023. The study was conducted in the Emergency department of Sheikh Zayed Hospital, Rahim Yar Khan. Data was collected by filling a questionnaire after interview of patients. Frequency of motor cycle related injuries and their pattern were noted. Informed consent was taken. Data was coded and analyzed by using SPSS version 27. Results: Total Injured patients included in the study were 372, out of which 87.4% were males and 12.6% were females. 44.5% of the injured falling within the 18-34 years of age range. The study shows that 35.5% injured were uneducated and not following proper safety measures. The majority of injured (65.1%) sustained major trauma, Involving head injuries and limbs fractures. The high proportion of major trauma causes burden on health system. Conclusion: Major causes of accidents in motorcyclists were not following safety measures, over speeding, not wearing helmets and poor enforcement of traffic laws. Observance of safety precautions, strict adherence to traffic rules and regulations are mandatory to avoid any possible accident. A national effort is required for the prevention of accidents to conserve human life and the financial resources of the country. Keywords: Motorcycle, RTA, Trauma, Helmet, Burden